Upaya Supervisor dalam Menerapkan Standar Recipe di Chadis Roof Bar Hotel Swiss Belinn Legian Kuta-Bali - Arini, Ni Nyoman; Pratama, I Putu Aris Wira; Putra, I Nengah Sandhi Artha (Universitas Triatma Mulya, 2023)
This research has a background problem, namely the bartender in making mixed drinks has not followed the standard recipe such as the method used, the ingredients used include the quality and dosage, and the tools used. Therefore, the author raised the title of the research on Supervisor Efforts in Implementing Recipe Standards at Chadis Roof Bar Hotel Swiss Belinn Legian, Kuta-Bali. The purpose and benefits of the author are to find out the procedures for making drinks, the obstacles faced by the bartender, and the efforts made by the supervisor in implementing the standard recipe at the Chadis roof bar Swiss Belinn Legian hotel, Kuta-Bali. In this study, there are several theories related to the research, namely the theory of hotels, bars and their equipment, efforts, bartenders, implementation, supervisors, standard recipes, and drinks. Using research instruments to improve research results. Data collection techniques by means of observation, interviews, and documentation. To overcome the problem where the bartender does not apply standard recipes, supervisors hold training every two to three months by providing material on SOPs and standard recipes. Supervisors also supervise during operating hours at the bar